Convergent Routes to Pyrroles Exploiting the Unusual Radical Chemistry of Xanthates – An Overview - Quiclet-Sire, Béatrice; Zard, Samir Z. (Synlett, 2017)
Convergent routes to a variety of pyrroles involving radical additions of xanthates are described. Emphasis is placed on reactions leading to the formation of 1,4-diketones or 1,4-ketoaldehydes or their synthetic equivalents, which can then be condensed with ammonia or primary amines in a variation of the classical Paal–Knorr synthesis of pyrroles. The modification of pyrroles by direct radical addition is also discussed.1 Introduction2 Earlier Routes to Pyrroles3 The Xanthate Radical Addition–Transfer Process4 Application to Pyrrole Synthesis5 Further Variations6 Direct Modification of Existing Pyrrole Rings7 Outlook and Perspectives
Keywords: pyrroles; Paal–Knorr reaction; 1,4-diketones; radical addition; xanthates